Wykonaj działania
a)(x/x-4)-(x+1/4-x)-(2x+3/x-4)=
b)(x+1/x-3)+(x+2/3-x)-(x+3/-3-x)=
c)(x-3/2x-2)-(x+4/2x+2)=
d)(1/x-2)-(1/x)-(1/x²-2x)=
e)(3x²+3x/x²-1)-(x-1/6x)=

te dzialania w nawiasach powinny być zapisane w postaci ułamka zwykłego.

2

Odpowiedzi

2010-04-05T17:25:46+02:00
A) (x/x-4)-(x+1/4-x)-(2x+3/x-4)= 1/2 - 2/x
b)(x+1/x-3)+(x+2/3-x)-(x+3/-3-x)=2-2/x+(x+1)/3
c)(x-3/2x-2)-(x+4/2x+2)=-0,5-x-1/2x
d)(1/x-2)-(1/x)-(1/x²-2x)=-2-1/x²-2x
e)(3x²+3x/x²-1)-(x-1/6x)=3x²+3/x-5/6x
2010-04-05T17:52:53+02:00